The Effect of the Acupressure Method on Common Cold in Infants Aged 6-12 Months in the Binjai Kota Health Center Work Area in 2019 - Purnama Handayani; Risky Novianty; Sri Kurnia (Science Midwifery, 2020)
Cold cough (common cold) is an upper respiratory tract disorder that most often affects infants and children. Because a cold cough experienced by a child can disturb the child, an acupressure method is needed to prevent and treat a common cold, the aim of this study is to determine whether there is an effect of the acupressure method on common cold in infants aged 6-12 months in the region. The work of Puskemas Bijai Kota in 2019. This study used a quantitative research type research design with a pre-experimental design. All babies aged 6-12 months in the Binjai Kota Puskemas in 2019 from January to April were 52 babies, with the sampling technique of accidental sampling. The data analysis technique was performed using the Wilcoxon test statistical analysis. There is a significant effect of the acupressure method on cold coughs (common cold) in infants aged 6-12 months in the work area of ​​the City Bijai Health Center in 2019, with p value = (0.000) <(0.050). Based on the results of this study, it can be concluded that there is a significant effect of the acupressure method on common cold in infants aged 6-12 months in the work area of ​​Puskemas Bijai Kota in 2019, where acupressure method is needed in the prevention of common cold.